Communication Theories and Types of Communication Innovative Methods of Involving People With Disabilities in Music - Baltabayevich, Nuraliyev Salahitdin (Researchparks Publishing, 2026)
In recent decades, the issue of involving people with disabilities in education and culture has been considered one of the important factors of human rights, social inclusion and sustainable development. Music education is considered a powerful pedagogical mechanism that not only satisfies the aesthetic needs of people with disabilities, but also reveals their psychological stability, social integration and creative potential. The article emphasizes the role of music in cognitive development, the formation of communicative skills and ensuring emotional stability.